Social Media Marketing and Consumer Brand Engagement: Elevating Luxury Perfume Brand Equity - Rossanty, Yossie; Rini, Endang Sulistya; Sembiring, Beby Karina Fawzeea; Silalahi, Amlys Syahputra (International Review of Management and Marketing, 2024)
The current research explores how consumer brand engagement (CBE) serves as a mediator between social media marketing (SMM) and consumer- based brand equity (CBBE) within the context of luxury perfume brands. Using a quantitative approach, data was collected from 322 participants who possess substantial knowledge of luxury perfume brands and are actively involved on social media platforms. The study employed partial least squares structural equation modeling (PLS-SEM) to analyze the relationships among SMM, CBE, and CBBE constructs. Through thorough analysis, the study establishes significant positive correlations between CBE and CBBE, identifying cognition, emotion, and behavior as pivotal dimensions of CBE that contribute to the formation of CBBE. Furthermore, the research confirms the impact of various SMM dimensions—including entertainment, interaction, personalization, trendiness, and word of mouth—on CBBE components such as brand loyalty, perceived quality, and brand awareness/ associations. Additionally, it validates a direct link from SMM to CBE, where compelling content enhances consumer engagement. The study also verifies a sequential relationship from SMM to CBE and subsequently to CBBE. Theoretical and practical implications are discussed, emphasizing the importance of comprehending and leveraging consumer engagement and SMM dynamics to bolster brand equity in the luxury perfume sector. The study identifies limitations and suggests future research directions to guide further investigation into these relationships.